Teacher professional learning to strengthen culturally nourishing pedagogies in Nunatsiavut area schools - Andersen, Ola; Pottle, Colleen; Dicker, Shannon; Moore, Sylvia; Tulloch, Shelley (2002)
Video version of conference presentation This presentation on professional learning for culturally nourishing pedagogies in Inuit schools is based on a SSHRC-funded research project which asked, how can collaborative professional learning (PL) foster knowledge and skills in culturally nourishing and sustaining pedagogical practices? In this presentation, three Inuit community-based researchers, including an Inuit teacher, a retired Inuit teacher, and an Indigenous program specialist, discuss the research process, outcomes, and next steps. SSHRC Partnership Engage Grant